Improving Students' Learning Interest Through Word Wall Net Media In State Children's Paud In The 2024/2025 Academic Year - Wahyuni Hasan; Ana Mulyono; Lalu Marzoan (Jurnal Ilmiah Mandala Education (JIME), 2025)
The purpose of this study was to increase student learning interest through word wall media in early childhood education in Jambianom Hamlet, Medana Village. With class action research methods and data analysis techniques Milles and Hubberman using 4 stages namely planning, action, observation and reflection.The results of the research on increasing children's interest in learning from pr-cycle, cycle I to cycle II show a change or increase in children's interest in learning using word wall net media. This is a form of results and evidence that there is a positive impact resulting from learning by using word wall net media because at the pre-cycle meeting of children's learning interest there were only 21% of children with Completed criteria, and 79% of children in the criteria Not Completed. Then in cycle I there was an increase in the ability of children's interest in learning increased by 31.6%, so that the ability of children's interest in learning in cycle I was completed by 52.6%, and stated that it was not completed by 47.4%. While in cycle II there was another increase of 31.6% so that the increase in children's interest in learning in cycle II was 84.2%, because in cycle II the ability of children's interest in learning had reached the classical criteria, the increase in children's interest in learning was sufficient until cycle II.